Choroidal vascular index in patients with open angle glaucoma and preperimetric glaucoma - Park, Yuli; Cho, Kyong Jin (PloS one, 2019)
To evaluate choroidal structural changes in glaucoma using choroidal vascularity index (CVI) compared to healthy subjects. This retrospective study included 56 patients with open angle glaucoma (OAG), 50 patients with preperimetric glaucoma (PPG) and 50 age-matched healthy eyes. Choroidal images were binarized into luminal area (LA) and stromal area. CVI was defined as the ratio of LA to total circumscribed choroid area (TCA). Mean choroidal thickness (CT) and mean CVI between glaucoma patients and healthy subjects were compared. OAG and PPG eyes showed smaller LA (0.45 ± 0.13 ㎟ vs. 0.47 ± 0.11 ㎟, p = 0.04). In multivariate regression analysis, CVI of both OAG (64.34±0.19%, p = 0.001) and PPG (65.37±0.15%, p = 0.001) were significantly lower than healthy eyes (68.81±0.14%). Eyes with glaucoma demonstrated reduced CVI compared with healthy eyes. CVI may be a potential noninvasive tool for studying vascular dysfunction in glaucoma.